Analisis Postur Kerja Menggunakan Metode REBA pada Mekanik Bengkel di PT. Mitra Pratama Mobilindo Sleman - Ihsan, Auliya; Yuamita, Ferida (Al-DYAS, 2025)
Vehicles play an important role in the mobility of the economic sector,the automotive industry is one of the main pillars of the Indonesian economy.PT Mitra Pratama Mobilindo Sleman is a well-known workshop that offers repair services, car sales, and spare parts.Mechanics in this increases the risk of fatigue,muscle injury,and muscle disorders. To find the risks and provide suggestions for improvement, this study uses the REBA (Rapid Entire Body Assessment) method to analyze the working postures of mechanics. Data was collected through observation, photo documentation of workers, and Nordic Body Map (NBM) questionnaire. Based on the results of the analysis, the work postures performed showed a significant risk of injury as indicated by the high REBA score, namely in the work postures of grease up, hydraulic repair, and diesel filter replacement. To reduce the risk of musculoskletal disorders, it is necessary to make recommendations for improving work postures based on the results of REBA calculations. The improvements include the use of small chairs and tools such as car creepers and the design of more ergonomic work postures.The results showed a significant decrease in REBA scores after the analysis of the proposed improvements. This indicates that the ergonomic risk value of the proposed improvements if implemented will improve the safety and health of mechanical workers and optimize the quality of work in automotive workshops.